An Analytical Study to Assess the Effect of KalushaPrasadanDravya in Purification of Water W.S. R. to Gomeda - Dayal, Shambhu; Samagandi , Kashinath (International Research Journal of Ayurveda & Yoga, 2024)
Water is the most important environmental factor for human survival. Without water man cannot survive more than 5 days. Water is essential and predominant constituent of cell protoplasm. Absence of clean water and sanitation are major risk for health. In developing countries water quality remains the major concern. In today era, it is time to look over the natural ancient concept which purified the water thousand years ago. Ayurveda especially Sushruta Samhita emphasize the various methods of purification of water on the basis of the amount of contamination. So, here an attempt made to evaluate the effect of Gomeda among the Sapta Kalusha Prasadana Dravya in yielding the potable water. The Sample of untreated water was collected from the Bisalpureservoir in 05 liter of sterilized water cane and the testified Gomeda was purchased from the authorized merchant. There are significant changes seen in physical, chemical parameters after the treatment of raw water with Gomeda. It is concluded that the worked on physical parameters of water.